A dose escalation study of RO6870810/TEN-10 in patients with acute myeloid leukemia and myelodysplastic syndrome. Issue 7 (7th June 2021) - Roboz, Gail J.; Desai, Pinkal; Lee, Sangmin; Ritchie, Ellen K.; Winer, Eric S.; DeMario, Mark; Brennan, Barbara; Nüesch, Eveline; Chesne, Evelyne; Brennan, Laura; Lechner, Katharina; Kornacker, Martin; et al.
Abstract: Bromodomain and extra-terminal (BET) proteins can drive carcinogenesis and therapy resistance. RO6870810 (RO) is a novel, small-molecule BET inhibitor. We conducted a study in 32 patients with relapsed/refractory acute myeloid leukemia and hypomethylating agent–refractory myelodysplastic syndrome (NCT02308761). Pharmacodynamic assessments showed decreases in CD11b in peripheral blood mononuclear cells at RO concentrations above 120 ng/mL. Treatment emergent adverse events were generally mild and the most frequent were fatigue, injection site reactions, diarrhea, decreased appetite and nausea. There were no treatment-related deaths. Potential drug-related dose limiting toxicities included decreased appetite, congestive cardiac failure, hypertension, fatigue, increased conjugated bilirubin and increased gamma glutamyltransferase. One AML patient achieved complete remission after withdrawal from study. Eleven AML patients experienced SD. For AML, the median OS was 72.0 days. For MDS, two patients experienced SD. Further development of RO as monotherapy was discontinued due to lack of efficacy, but combinations with other agents are under consideration.